Left-wing militancy and homelessness in the Popular Unity government: Political alliances for access to housing in the city of Osorno - Eyzaguirre Jorquera, Daniel (2026)
This research analyzed the impact of the political alliances generated between militants of leftist political parties and homeless settlers in the development of land seizures and the organization of camps that occurred in the context of the Popular Unity government in the city of Osorno, Chile. The research methodology was based mainly on the application of semi-structured interviews with subjects who participated as militants or settlers in those processes. The results indicate that the site occupations were a direct consequence of the formation of strategic political alliances between settlers and leftist militants. Likewise, it was shown that while the leftist militants saw in the settlers a support base for their political projects, the settlers recognized in these partisan structures an opportunity for access to housing.